Listen : how to find the words for tender conversations / Kathryn Mannix. - Mannix, Kathryn (William Collins, 2021)
A child coming out to their parent. A family losing someone to terminal illness. A friend noticing the first signs of someone's dementia. A career's advisor encouraging a teenager to pursue their interests and stay out of trouble. There are moments when we must talk, listen and be there for one another. Why do we so often come away from those times feeling like we could have done more, or should have been braver in the face of discomfort? Why do we skirt the conversations that might matter most? By bringing together deeply moving stories with a lifetime's experience working in medicine and the newest psychology, Mannix offers lessons for how we can better speak our mind and help when others need to.